2016
DOI: 10.1177/0734242x16654979
|View full text |Cite
|
Sign up to set email alerts
|

Corn forage biological pretreatment by Trametes versicolor in a tray bioreactor

Abstract: Trametes versicolor is a white-rot fungus known to be efficient in lignin removal due to its complex extracellular lignocellulolytic enzymatic system. Therefore, it can be used in the treatment of lignocellulose waste from agro, food, and wood industries. In a first experiment, corn forage treatment with T. versicolor was investigated in laboratory jars. In a second experiment, the process was scaled up to a tray bioreactor. In the tray bioreactor, the process of lignin degradation was improved, resulting in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…Silva Canedo et al . reported that the initial moisture content increased during 18 days of fermentation, which was also found previously when corn silage was used as a substrate for T. versicolor solid‐state cultivation . However, in this work, the moisture content after 14 days of fermentation decreased from the initial 62.7% to a final content of 57.9%, which can be explained by the water evaporation being slightly faster than water generation during solid‐state fermentation.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Silva Canedo et al . reported that the initial moisture content increased during 18 days of fermentation, which was also found previously when corn silage was used as a substrate for T. versicolor solid‐state cultivation . However, in this work, the moisture content after 14 days of fermentation decreased from the initial 62.7% to a final content of 57.9%, which can be explained by the water evaporation being slightly faster than water generation during solid‐state fermentation.…”
Section: Resultssupporting
confidence: 77%
“…More than 20 mL of water was not appropriate for T. versicolor cultivation, as described by Planinić et al . .…”
Section: Resultsmentioning
confidence: 99%
“…90 This ability is due to the fact that white-rot fungi produce a variety of enzymes, such as lignin peroxidases, manganese-dependent peroxidases, and laccases that degrade the lignin. 91 Planinić et al 92 treated lignocellulose waste from the agro-, food and wood industries for 7 days with T. versicolor, which resulted in lignin conversion up to 71 %. Tišma et al 93 studied Trametes versicolor growth on glucose, fructose, and sucrose, and developed a mathematical model of the process composed of sucrose hydrolysis catalyzed by intracellular enzyme, and microbial growth on glucose and fructose.…”
Section: Biological Pretreatmentmentioning
confidence: 99%
“…After the treatment with T. versicolor, the amount of ash and protein generally increased in all the three oil cakes, where the highest increase of ash (40%) and protein (53%) was recorded in flaxseed oil cake (Table 4). The increase of soluble carbohydrates in flaxseed oil cake is the consequence of the decrease of insoluble fibers, due to the activity of lignolytic enzymes produced by T. versicolor [29]. It is interesting to observe that total soluble carbohydrates in flaxseed oil cake increased by 509%.…”
Section: Chemical Analysis Of the Oil Cakes After Biological Treatmentmentioning
confidence: 96%
“…T. versicolor is known to be a good producer of lignolytic enzymes such as laccase [27] and was chosen for this study due to our previous experience with its solid-state cultivation on corn silage [28,29] and brewery spent grains [30]. The study aims to identify the possible pathways for the utilization of hull-less pumpkin, flax, and hemp oil cakes, before and after biological treatment.…”
Section: Introductionmentioning
confidence: 99%